DEVELOPMENT OF A WATER PURIFICATION DEVICE WITH ELECTROCOAGULATION PROCESS AS A LEARNING MEDIUM FOR WATER TREATMENT MATERIALS - Ovie Sari Wulan; Yoga Alfarizi; Dedek Fatjri; Yuni Fatisa; Zona Octarya (EDUPROXIMA : Jurnal Ilmiah Pendidikan IPA, 2026)
Water treatment materials are often considered abstract and complex for students to understand. Relevant technologies, such as electrocoagulation (EC), have not been optimally integrated in learning. This study aims to develop and evaluate the feasibility of an electrocoagulation prototype-based learning medium designed to bridge these pedagogical gaps. Using the Research and Development (RD) method with an adaptation of the Borg and Gall model, feasibility data were collected through expert validation and practicality questionnaires, then analyzed using quantitative descriptive statistics. The results show that the media is Very Valid (average score of 91.53%) and Very Practical (89.23%). Furthermore, the prototype received a Very Interesting response from students (90.07%), indicating strong engagement potential. This medium successfully concretizes abstract concepts such as redox reactions and flocculant formation into tangible, real-time phenomena, effectively bridging the gap between conventional methods and modern industrial technology. It is concluded that this prototype is a valid and innovative tool for chemistry education, with significant potential for future integration with IoT-based sensors to enhance data-driven STEM learning further.